1988
DOI: 10.3109/00498258809041652
|View full text |Cite
|
Sign up to set email alerts
|

The use of single sample clearance estimates to probe hepatic drug metabolism in rats. II

Abstract: 1. Single sample clearance estimates, Cl, were calculated for each of five drugs employed as probes of hepatic drug-metabolizing activity in rats. Probe drugs were theophylline, phenytoin, valproic acid, antipyrine, and S-warfarin. Cl values were calculated for each probe in animals pretreated with phenobarbital, isosafrole, beta-naphthoflavone, or clofibrate. Control animals were pretreated with vehicle only. 2. A clearance index (c.i., probe Cl after pretreatment divided by probe Cl control) was calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Bachmann et al estimated the clearance of racethosuximide to be around 0.022 l/h/kg after a 35 mg/kg dose and 0.027 l/h/kg after a 5 mg/kg dose using an achiral analytical procedure (EMIT) [8,9]; these values are considerably lower than those observed in this present study. Bachmann et al [9] also found the apparent volume of distribution to be 0.70+0.031 l/kg; these values were close to the lower end of the range observed in this current work.…”
Section: Pharmacokinetic Parameterscontrasting
confidence: 56%
“…Bachmann et al estimated the clearance of racethosuximide to be around 0.022 l/h/kg after a 35 mg/kg dose and 0.027 l/h/kg after a 5 mg/kg dose using an achiral analytical procedure (EMIT) [8,9]; these values are considerably lower than those observed in this present study. Bachmann et al [9] also found the apparent volume of distribution to be 0.70+0.031 l/kg; these values were close to the lower end of the range observed in this current work.…”
Section: Pharmacokinetic Parameterscontrasting
confidence: 56%
“…where D represents the dose of probe drug in mg/kg; V is volume of distribution (1/kg); t is the sampling time (h); and Ct is the plasma concentration of the drug (mg/1) at time t. This method of determining single sample clearance estimates (CL) has been described previously [15].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Blood samples were drawn at previously determined sampling times which permitted probe clearances to be estimated from single measurements of probe concentrations in plasma as previously described [15]. Post-dose sampling times were as follows: theophylline.…”
Section: Blood Samplingmentioning
confidence: 99%
“…Theophylline CL was estimated from plasma con centration measurements in samples acquired from blood drawn 6 h after theophylline administration ac cording to the following equation [5]:…”
Section: Theophylline Administration and Measurementmentioning
confidence: 99%